2008
DOI: 10.1016/j.neuropharm.2007.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Input-specific plasticity at excitatory synapses mediated by endocannabinoids in the dentate gyrus

Abstract: SummaryEndocannabinoids (eCBs) mediate transient and long-lasting synaptic plasticity in several brain structures. In the dentate gyrus, activation of the type 1 cannabinoid receptor (CB1R) by exogenous ligands reportedly depresses excitatory synaptic transmission. However, direct evidence of eCB signaling at excitatory synapses in this region has been lacking. Here, we demonstrate that eCB release can be induced by a brief postsynaptic depolarization of dentate granule cells (DGCs), which potently and transie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
62
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 57 publications
(98 reference statements)
11
62
1
1
Order By: Relevance
“…However, it has been controversial as to the role of 2-AG or DGL in eCB-mediated retrograde suppression at MC-GC synapses (Chiu and Castillo, 2008). In the present study, we have demonstrated that DSE and its enhancement by group I mGluR activation were abolished in DGL␣-knock-out mice (Fig.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…However, it has been controversial as to the role of 2-AG or DGL in eCB-mediated retrograde suppression at MC-GC synapses (Chiu and Castillo, 2008). In the present study, we have demonstrated that DSE and its enhancement by group I mGluR activation were abolished in DGL␣-knock-out mice (Fig.…”
Section: Discussionsupporting
confidence: 51%
“…The electrode had a tip separation of 40 m and was placed in the supragranular layer within 40 m from the cell body layer. A previous report (Chiu and Castillo, 2008) showed that medial perforant path inputs, but not MC inputs, were sensitive to group II mGluR agonists. Therefore, we checked whether the evoked EPSCs were suppressed by 1 M DCG-IV (group II mGluR agonist), and only the DCG-IV-insensitive EPSCs were analyzed.…”
Section: Methodsmentioning
confidence: 89%
See 2 more Smart Citations
“…A EC-STD subclassifica-se em: a) supressão da inibição/excitação induzida pela despolarização (depolarization-induced suppression of inhibition/excitation, DSI/DSE), conforme induzida em neurônios inibitórios/excitatórios 24,27,28,38,39,42,47,[51][52][53][54][55] ; b) supressão mediada por receptores ionotrópicos NMDA (NMDA-R-EC-STD) 39,42 ; c) supressão mediada por receptores metabotrópicos (metabotropic-induced suppression of inhibition/excitation, MSI/MSE) 24,38,39,42 ; sobretudo receptores metabotrópicos glutamatérgicos tipo 1 e tipo 5 (mGlu-R 1 /-R 5 ) e receptores metabotrópicos colinérgicos muscarínicos tipo 1 e tipo 3 (mAChR-M 1 /-M 3 ) -mediado, metabotrópico-mediado e comediado) 28,37,38,48,60,63 . O mecanismo metabotrópico--mediado é efetivado pelo 2-AG 38,48,63 , com duas exceções.…”
Section: Ec-std/-ltd: Mecanismos Pós-sinápticosunclassified